Recovery after a running training session: influence of exercise characteristics, hot-water immersion, and cold-water immersion - Dutra, Yago Medeiros [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Running is one of the most widely used efforts in conditioning routines, however, the characteristics and time-course of fatigue after running at different intensities and/or types of execution (i.e., continuous or interval) have not yet been described. Moreover, fatigue is known to be task-dependent, whereby its characteristics and causal mechanisms will be influenced by aspects of exercise. In this way, due to discrepancies in basic mechanisms of action between cold-water immersion (CWI) and hot-water immersion (HWI), it is possible that their effectiveness in optimizing recovery after running may be influenced by aspects of the exercise performed and the characteristics of the fatigue established. Accordingly, the overall aim of this thesis was to investigate the influence of aspects of exercise, CWI and HWI on the fatigue-recovery continuum after running. To achieve this aim, a methodological study and three experimental studies were carried out. From the data gathered, we observed that: i) neuromuscular function assessment protocol involving maximal voluntary isometric contractions of the knee extensors, peripheral stimulation and monitoring of electromyography activity provides outcomes with a coefficient of variation <10% and repeatability <25% within day and between days; ii) even with equalized volume, peripheral fatigue and perceived fatigability are more pronounced after high-intensity interval exercise performed 50% above the velocity associated with the respiratory compensation point (vRCP; HIIT150%RCP) compared to exercise performed continuously at the velocity associated with vRCP (CONT100%RCP); however, central fatigue was greater after CONT100%RCP compared to HIIT150%RCP; iii) regardless of the characteristics of the effort, running 8-km causes impairments on neuromuscular function, cardiac parasympathetic activity, mood, cognitive function and greater physiological/psychological stress in successive brief effort for at least 6 hours after exercise; however, HIIT150%RCP caused greater impairment in dynamic neuromuscular function and greater perceived fatigability during successive brief efforts compared to CONT100%RCP, while high-intensity interval exercise performed 30% above vRCP (HIIT130%RCP) caused greater reduction in resting cardiac parasympathetic activity compared to CONT100%RCP; iv) both CWI and HWI were able to mitigate central fatigue after running compared to placebo and passive rest, but CWI only had this ability after HIIT150%RCP, while HWI only had this ability after CONT100%RCP; neither method mitigate the impairments in maximal voluntary isometric force production or tissue contractility of knee extensors; however, after both HIIT150%RCP and CONT100%RCP, CWI was able to increase resting cardiac parasympathetic activity and HWI was able to decrease cardiorespiratory demand during successive brief efforts compared to placebo and passive rest. In view of the data obtained, it was concluded that the intensity/type of running has an impact on the characteristics of fatigue and that the CWI and HWI for optimize recovery should be used taking into account the characteristics of the running performed and the recovery metric to be improved.

A corrida é um dos esforços mais utilizados em rotinas de condicionamento, contudo, as características e curso temporal da fadiga após corrida de diferentes intensidades e tipo de execução (i.e., contínua ou intervalada) ainda não foram descritos. Além disso, a fadiga é tarefa-dependente, ou seja, suas características e mecanismos causais são influenciados por aspectos do exercício. Desse modo, devido a discrepâncias em mecanismos de ação básicos entre a imersão em água fria (CWI) e a imersão em água quente (HWI), é possível que as suas eficácias em otimizar a recuperação após corrida possam ser influenciadas pelas características do exercício realizado e da fadiga instaurada. Diante desse contexto, o objetivo geral da presente tese foi investigar a influência de aspectos do exercício, da CWI e da HWI sobre o continuum fadiga-recuperação após corrida. Para alcançar tal objetivo, um estudo de caráter metodológico e três estudos experimentais foram realizados. A partir dos dados reunidos, observamos que: i) desfechos sobre a função neuromuscular obtidos por meio de teste envolvendo contrações voluntárias isométricas máximas dos extensores do joelho, estimulação periférica e monitoramento da atividade de eletromiografia apresentam coeficiente de variação <10% e repetibilidade <25% dentro do dia e entre dias; ii) mesmo com volume equalizado, a fadiga periférica e a fatigabilidade percebida são mais pronunciadas após exercício intervalado de alta intensidade realizado 50% acima da velocidade associada ao ponto de compensação respiratório (vRCP; HIIT150%RCP) em comparação à exercício realizado de forma contínua na vRCP (CONT100%RCP); no entanto, a fadiga central foi maior após CONT100%RCP em comparação ao HIIT150%RCP; iii) correr 8-km, independentemente das características do exercício, acarreta prejuízos à função neuromuscular, atividade parassimpática cardíaca em repouso, alterações no humor e em aspectos cognitivos, e maior estresse fisiológico/psicológico durante esforços breve subsequentes por pelo menos 6-horas após o fim do exercício; no entanto, o HIIT150%RCP acarretou maior prejuízo à função neuromuscular e maior fatigabilidade percebida durante esforços breves subsequentes em comparação ao CONT100%RCP, enquanto o exercício intervalado de alta intensidade realizado 30% acima da vRCP (HIIT130%RCP) acarretou maior redução da atividade parassimpática cardíaca em repouso em comparação ao CONT100%RCP; iv) ambas CWI e HWI foram eficazes em atenuar a fadiga central após corrida em comparação à intervenção placebo e descanso passivo, contudo, a CWI só acarretou tal efeito benéfico após o HIIT150%RCP enquanto a HWI somente após o CONT100%RCP; nenhum dos métodos atenuou os prejuízos à produção de força voluntária isométrica máxima ou à contratilidade tecidual; no entanto, após ambos HIIT150%RCP e CONT100%RCP, a CWI foi capaz de aumentar a atividade parassimpática cardíaca em repouso e a HWI foi capaz de reduzir a demanda cardiorrespiratória durante esforços subsequentes em comparação à intervenção placebo e descanso passivo. Diante dos dados obtidos, concluiu-se que a intensidade/tipo de execução da corrida impactam as características da fadiga após exercício e que a CWI e da HWI devem ser usadas para otimizar a recuperação após a corrida considerando as características do exercício que foi realizado e as métricas de recuperação que se deseja otimizar.
Recuperação após uma sessão de treino de corrida: influência das caraterísticas do exercício, imersão em água quente e imersão em água fria
Keywords: Muscle fatigue; Post-exercise recovery; Exercise performance; Fadiga muscular; Recuperação após exercício; Desempenho físico